2016
DOI: 10.1115/1.4032663
|View full text |Cite
|
Sign up to set email alerts
|

Lumped Capacitance and Three-Dimensional Computational Fluid Dynamics Conjugate Heat Transfer Modeling of an Automotive Turbocharger

Abstract: One-dimensional wave-action engine models have become an essential tool within engine development including stages of component selection, understanding system interactions, and control strategy development. Simple turbocharger models are seen as a weak link in the accuracy of these simulation tools, and advanced models have been proposed to account for phenomena including heat transfer. In order to run within a full engine code, these models are necessarily simple in structure yet are required to describe a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Such is the case of the heat transfer effects, that can be determined experimentally with a simple lumped model as in 9 or 10 . The simplifications that are used in simple turbocharger heat transfer models that are coupled with one-dimensional gas dynamics codes have been validated both experimentally and with computational fluid dynamics (CFD) simulations, as in 11 . The results of including a heat transfer model to determine internal heat flows has been investigated by several authors, such as in the works by Olmeda et al 12 or Serrano et al 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such is the case of the heat transfer effects, that can be determined experimentally with a simple lumped model as in 9 or 10 . The simplifications that are used in simple turbocharger heat transfer models that are coupled with one-dimensional gas dynamics codes have been validated both experimentally and with computational fluid dynamics (CFD) simulations, as in 11 . The results of including a heat transfer model to determine internal heat flows has been investigated by several authors, such as in the works by Olmeda et al 12 or Serrano et al 13 .…”
Section: Introductionmentioning
confidence: 99%
“…8 Other aspects of the turbocharger behaviour can be taken into account in these simulations. Such is the case of the heat transfer effects, which can be determined experimentally with a simple lumped model as in Bohn et al 9 or Serrano et al 10 The simplifications that are used in simple turbocharger heat transfer models that are coupled with 1D gas dynamics codes have been validated both experimentally and with computational fluid dynamics (CFD) simulations, as in Burke et al 11 The results of including a heat transfer model to determine internal heat flows has been investigated by several authors, such as in the works by Olmeda et al 12 or Serrano et al 13 These models can even be used to obtain information that is difficult to measure in an experiment, such as the difference in heat flow paths, as in the work by Aghaali et al 14 Friction losses models as the one developed by Serrano et al 15 or Marelli et al 16 have been also coupled with 1D gas dynamics codes so the mechanical efficiency can be computed in time marching simulations, as shown in Serrano et al 17 Several works about radial turbine modelling can be found in the literature, where the properties of the internal flow of the turbine under different boundary conditions are presented and discussed, as can be seen in the works by Galindo and Colleagues 18,19 and Hakeem et al 20 Especially focused in the unsteady performance at high frequencies are the works by Hu 21 and King. 22 Also, the experimental characterisation of turbochargers increases in complexity in parallel to the models that use this information.…”
Section: Introductionmentioning
confidence: 99%
“…The assumptions made in lumped capacitance models or other 1-D models should be validated in order to have a basis. This validation could be done by conducting focused experiments or 3-D CHT model [34]. Such validation is essential in strengthening the many results found in the literature which are generated by 1-D models.…”
Section: One-dimensional Modelmentioning
confidence: 96%
“…The temperature distribution obtained from the CHT method is used for the structural analysis using the finite element method (FEM) to determine the thermal stress/strain of turbocharger parts under thermal load [33]. Increasing number of researches on heat transport in turbochargers is studied through CHT [34,35]. Individual components such as turbine, compressor and bearing housing along with full turbocharger analyses are also done using CHT [35,36].…”
Section: Three-dimensional Numerical Simulationmentioning
confidence: 99%
“…During the last decades, increasingly advanced turbocharger models have been developed for sizing, engine matching and one-dimensional modeling [4]. All the interesting phenomena are currently considered with high accuracy: adiabatic map extrapolation of both turbine [4] and compressor [5], friction losses [6] and heat transfer effects [7], can be computed hundreds of times per second with commodity hardware. All of these sub-models are based on zero-or onedimensional approaches and are used in a whole engine model simulation to improve the predictions [8].…”
Section: Introductionmentioning
confidence: 99%